2018
DOI: 10.1007/s00431-018-3172-4
|View full text |Cite
|
Sign up to set email alerts
|

First report on the nationwide incidence of type 1 diabetes and ketoacidosis at onset in children in Serbia: a multicenter study

Abstract: This is the first study reporting the nationwide incidence of T1DM and alarmingly high prevalence of DKA at diagnosis in youth in Serbia. The focus of public health preventive measures should be directed towards the preschoolers, considering the highest frequency and severity of DKA observed in this age group. What is Known: • Knowing regional T1DM incidence is of paramount importance for resource allocation and healthcare services provision. • DKA is the leading cause of acute mortality in youth with T1DM, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
2
7
0
4
Order By: Relevance
“…Only 68% of centres reported adoption of the ISPAD guidelines to manage DKA, and there was great variation in the approach to management 1. These data were consistent with a comprehensive study of DKA incidence during a 10-year follow-up in Italy by Cherubini et al ,2 and with studies published in the same period in other European3–5 and Extra European countries 6 7…”
Section: Introductionsupporting
confidence: 71%
“…Only 68% of centres reported adoption of the ISPAD guidelines to manage DKA, and there was great variation in the approach to management 1. These data were consistent with a comprehensive study of DKA incidence during a 10-year follow-up in Italy by Cherubini et al ,2 and with studies published in the same period in other European3–5 and Extra European countries 6 7…”
Section: Introductionsupporting
confidence: 71%
“…The Poisson regression resulted that younger children (0–4 years old) are significant more affected of ketoacidosis than older children. Similar results were found in a study of type 1 diabetes among Serbian children Vukovic et al [29].…”
Section: Discussionsupporting
confidence: 91%
“…15,16 However, high frequency of DKA among children with T1DM was reported in countries such as Egypt, Serbia, Saudi Arabia, USA, UK and others. [17][18][19][20][21][22][23][24] The current study showed a trend of increase in the severity of DKA among children with T1DM over the study period with an overall frequency of 12.3%. This frequency is comparable to that reported in Kuwait, Spain, France, Finland and Italy.…”
Section: Discussionmentioning
confidence: 87%